Sintesis Nanopartikel ZnO Menggunakan Prekursor ZnCl2 dan Polimer Penstabil Tween 80 untuk Aplikasi Tabir Surya - Anisa Nurraeni Rozi; Horasdia Saragih (Jurnal Fisika Unand, 2025)
ZnO nanoparticles are semiconductor materials with a wide energy band gap (3.37 eV), making them excellent for use as sunscreen ingredients due to their superior ultraviolet protection properties. ZnO nanoparticles are superior to other conventional sunscreen materials because they do not cause skin irritation or allergies. The purpose of this study was to synthesize ZnO nanoparticles as a sunscreen material using Tween 80 stabilizing polymer and to comprehensively examine the effect of Tween 80 concentration on the characteristics of the resulting ZnO nanoparticle sunscreen. ZnO nanoparticles were synthesized using ZnCl2 and Tween 80 precursors with a Rotor Stator Homogenizer equipment system. Four different concentrations of Tween 80 were used to observe their effect on the characteristics of the resulting ZnO nanoparticles. The results showed that the average diameter of ZnO nanoparticles, their polydispersity index, and their zeta potential decreased as the concentration of Tween 80 used increased. Their optical transmittance was very high in the visible light spectrum and very low in the ultraviolet spectrum, especially for ZnO nanoparticles with the smallest average diameter (11.6 nm). This means that the visible light transmission and ultraviolet light absorption are excellent. In addition, the absorption edge is also very sharp. These three properties indicate that the ZnO nanoparticles produced are very suitable and have great potential for use as a sunscreen material.